Role of serum amylase and salivary cytokines in oral complications during chemoradiotherapy - Kawahara, Kenta; Hiraki, Akimitsu; Arita, Hidetaka; Takeshita, Hisashi; Hirosue, Akiyuki; Matsuoka, Yuichiro; Sakata, Junki; Obayashi, Yuko; Nakashima, Hikaru; Hirayama, Mayumi; Nagata, Masashi; Yoshida, Ryoji; et al. (Oral diseases, 2021)
Objectives To investigate whether serum amylase can predict the recovery of salivary volume and determine the correlation of the level of cytokines, including epidermal growth factor, hepatocyte growth factor and keratinocyte growth factor, with oral mucositis during chemoradiotherapy for oral cancer. Subjects and Methods This study included 84 patients treated with preoperative chemoradiotherapy followed by curative surgery, following a phase II study protocol. We measured and analysed the correlation of the stimulated saliva volume, serum amylase and cytokines in resting saliva at baseline and 1 month after chemoradiotherapy with oral mucositis levels. Results We observed a negative correlation between the serum amylase level at the beginning of chemoradiotherapy and the stimulated saliva volume at 1 month after chemoradiotherapy (p = .03). Epidermal growth factor in resting saliva was significantly reduced after chemoradiotherapy (p < .01). The incidence of severe oral mucositis during chemoradiotherapy was significantly higher and negatively associated with the epidermal growth factor and keratinocyte growth factor levels (p = .04, p = .05). Conclusions The serum amylase level at the beginning of chemoradiotherapy may be a predictor of the recovery of the saliva volume. Furthermore, cytokines such as epidermal growth factor and keratinocyte growth factor in resting saliva affect the development of oral mucositis during chemoradiotherapy.